PERKAWINAN DI BAWAH UMUR PERSPEKTIF HAM (Studi Kasus di Desa Bulungihit, Labuhan Batu, Sumatra Utara) - ., Nurhidayatuloh; Marlina, Leni (Islamic University of Indonesia, 2010)
Paper below highlights the phenomenon of early marriage or underage marriage is happening in the Village Bulungihit, Labuhan Batu, North Sumatra that is with so many marriages occur with age that is still relatively young, especially from the candidates wife. Marriage is the case because of the influence of culture, arranged marriages, lack of education, economy, society is too free, and the willingness of the children themselves. Parents assume if a woman can read and write was considered sufficient, no need to continue their education to the next level. Because girls will eventually go back to the kitchen as well. With regard to the regulation of marriage rights under this age can be considered to violate the human rights provisions. Moreover, by manipulating the age of marriage will solve the problem, instead, will actually create new problems with regard to psychological kekurangsiapan child who married a minor. For that countries should take firm action against violations of human rights Keywords: pernikahan, bawah umur, Sumatra Utara, dan HAM